A simplified model to enhance SMEs’ investment in renewable energy sources in Ghana - Karikari Appiah, Michael (International Journal of Sustainable Energy Planning and Management, 2022)
Although the Renewable Energy Act 2011 (Act, 832) was enacted to facilitate development and investment in the Renewable Energy sources in Ghana as part of the efforts to achieve Sustainable Development Goal 7, the actual impacts of the policy are yet to be felt as manifested in the amendment Act 2020 (Act, 1045). There is a need to develop an alternative model to enhance investment in the renewable energy sector. Drawing from the Resources Based View (RBV) and Porter’s Five Forces this paper is aimed to develop a simplified model to explain Small and Medium Enterprises (SMEs)investment determinants in the renewable energy sources in Ghana. We argued that the simplified integrated model provides robust predictability and wider generalization. Our paper is anchored on the positivists’ epistemology and quantitative methodology. Our hypotheses have been tested using cross-sectional data from the Ghanaian SMEs. Variance Based Partial Least Squares (PLS) method has been used to analyze the survey data. Our results indicate that entrepreneurial competency, financial resource, marketing capability, and technological usage significantly relate to investment in renewable energy. Moreover, the results have shown that competitive rivalry, the threat of entry, and bargaining power of customers significantly relate to investment in renewable energy. These results substantiate the well-known argument that industry forces and resource competitive strategies are significant determinants of a firm’s competitiveness and behavioral intentions. Overall, these results have theoretical and practical implications to facilitate the capacity of SMEs and create enabling renewable energy local content policy to enhance SMEs ’ participation in the sector.